(Invited) Plasma Synthesis of Conductive Carbon Based Nanomaterials. (21st April 2017) - Kovacevic, Eva; Hussain, Shahzad; Berndt, Johannes; Pattyn, Cedric; Strunskus, Thomas; Ammar, Mohammed-Ramzi; Canizarès, Aurelién; Simon, Patrick; Tatarova, Elena; Dias, Ana; Tessier, Pierre-Yves; Boulmer-Leborgne, Chantal
Abstract : We report in our work on the use of different plasma based synthesis methods of conductive carbon based nanomaterials. Since the application fields are widening, control and the understanding of the plasma is essential in order to control the synthesis of the targeted materials. Presented are results on the plasma and material diagnostics, enabling the use of plasma synthesized nanostructures in bioengineering.